2023
DOI: 10.1186/s12885-023-10541-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genomic features in patients with second primary glioblastoma following first primary renal cell carcinoma

Abstract: Purpose To explore the potential pathogenesis and clinical features of second primary glioblastoma (spGBM) following first primary renal cell carcinoma (fpRCC). Methods Patients with spGBM after fpRCC were enrolled from our institution and the SEER dataset. Sanger sequencing, whole genome sequencing, and immunehistochemistry were used to detect molecular biomarkers. Results Four and 122 cases from our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…[2] Different patterns of coincidental RCC and GBM have been reported, including both synchronous and metachronous presentations. [2,4,[8][9][10][11] Although no clear relationship between these two cancers has been elucidated, it has been suggested that they may cooccur due to therapeutic side effects, underlying genetic syndromes, or as an unfortunate coincidence.…”
Section: Commentsmentioning
confidence: 99%
See 4 more Smart Citations
“…[2] Different patterns of coincidental RCC and GBM have been reported, including both synchronous and metachronous presentations. [2,4,[8][9][10][11] Although no clear relationship between these two cancers has been elucidated, it has been suggested that they may cooccur due to therapeutic side effects, underlying genetic syndromes, or as an unfortunate coincidence.…”
Section: Commentsmentioning
confidence: 99%
“…[8,11] However, Zhang et al were not able to confidently attribute GBM development to any specific therapeutic measure incurred during treatment for RCC, as none of the described patients received cranial radiotherapy, and the pharmacotherapy between patients was inconsistent. [11] In addition, Kim et al's description of an RCC occurring in a patient with existing GBM does not show a relationship between GBM treatment and RCC;…”
Section: Commentsmentioning
confidence: 99%
See 3 more Smart Citations